miR449a/SIRT1/PGC-1α Is Necessary for Mitochondrial Biogenesis Induced by T-2 Toxin - Ma, Shijie; Zhao, Yurong; Sun, Jianwei; Mu, Peiqiang; Deng, Yiqun (Frontiers in Pharmacology, 2018)
T-2 toxin is one of the type A trichothecenes produced mainly by the Fusarium genus. Due to its broad distribution and highly toxic nature, it is of great concern as a threat to human health and animal breeding. In addition to its ribotoxic effects, T-2 toxin exposure leads to mitochondrial dysfunction, reactive oxygen species (ROS) accumulation and eventually cell apoptosis. We observed that mitochondrial biogenesis is highly activated in animal cells exposed to T-2 toxin, probably in response to the short-term toxic effects of T-2 toxin. However, the molecular mechanisms of T-2 toxin-induced mitochondrial biogenesis remain unclear. In this study, we investigated the regulatory mechanism of key factors in the ROS production and mitochondrial biogenesis that were elicited by T-2 toxin in HepG2 and HEK293T cells. Low dosages of T-2 toxin significantly increased the levels of both mitochondrial biogenesis and ROS. This increase was linked to the upregulation of SIRT1, which is controlled by miR-449a, whose expression was strongly inhibited by T-2 toxin treatment. In addition, we found that T-2 toxin-induced mitochondrial biogenesis resulted from SIRT1-dependent PGC-1α deacetylation. The accumulation of PGC-1α deacetylation, mediated by high SIRT1 levels in T-2 toxin-treated cells, activated the expression of many genes involved in mitochondrial biogenesis. Together, these data indicated that the miR449a/SIRT1/deacetylated PGC-1α axis plays an essential role in the ability of moderate concentrations of T-2 toxin to stimulate mitochondrial biogenesis and ROS production.